Improving the Quality of Education at Madrasah Tsanawiyah Negeri Fakfak through Leadership Strategies implemented by the Head of Madrasah - Laenussa, Ratna; Amin, Surahman; Sudirman (Al-Riwayah : Jurnal Kependidikan, 2024)
The goal of this study is to assess how the Head of the MTsN Fakfak carries out their main roles and functions, identify the factors that assist or hinder the head of the Fakfak State Tsanawiyah Madrasah in improving the quality of education, and investigate the solutions implemented by the Madrasah Head to overcome obstacles to carrying out these primary tasks. The qualitative study draws on pedagogical, management, and theological approaches. Primary data was gathered from the madrasah head, teachers, administrative staff, and relevant individuals within the madrasah, while secondary data was collected from books, the internet, and other sources related to the research problem. Data collection methods included observation, interviews, and documentation studies. The study found that the head of MTsN Fakfak utilizes a democratic leadership style in fulfilling their main responsibilities, as evidenced by the active, dynamic, and purposeful strategies, actions, and programs that involve all stakeholders in advancing the institution. The leadership of the madrasah head has had a positive impact on the quality of education, but there are areas for improvement that require a more effective strategy for the madrasah head to fulfill their duties. The study suggests that as a leader, the head of the madrasah must continuously and optimally carry out their primary responsibilities to enhance the quality of education within the madrasah. Consequently,madrasah heads must adeptly mobilize resources in program planning and evaluation, curriculum development, learning, personnel management, learning facilities and resources, finance, student and community services, and fostering a conducive madrasah environment.